2012
DOI: 10.7314/apjcp.2012.13.3.775
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 8-isoprostane (8-isoPGF2α) in Urine of Non-Small Cell Lung Cancer (NSCLC) Patients Undergoing Chemotherapy

Abstract: Abstract8-isoprostane (8-isoPGF 2α ) is a reliable marker and considered a gold standard for lipid peroxidation. There are very few reports of 8-isoprostane levels in cancer patients, and in patients undergoing chemotherapy. Oxidative stress is however expected and has been observed in patients with cancer. This study measured 8-isoprostane levels in urine by ELISA of 25 patients undergoing chemotherapy for advanced non-small cell lung cancer, at cycles 1, 2, and 3 of treatment. It considers the creatinine cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…Patients undergoing chemotherapy for advanced non-small cell lung cancer showed increased (over 6-to 12-fold from baseline) 8-isoprostane concentration in urine during chemotherapy with cisplatin, an extremely cytotoxic drug [6]. However, immediately after chemotherapy for breast cancer, 8-isoprostane concentration is similar to that in healthy individuals [39].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Patients undergoing chemotherapy for advanced non-small cell lung cancer showed increased (over 6-to 12-fold from baseline) 8-isoprostane concentration in urine during chemotherapy with cisplatin, an extremely cytotoxic drug [6]. However, immediately after chemotherapy for breast cancer, 8-isoprostane concentration is similar to that in healthy individuals [39].…”
Section: Discussionmentioning
confidence: 96%
“…The antioxidant capacity is likely to be greater among individuals with low oxidative status prior to the chemotherapy and the contribution of ROS downregulation greater among those with higher oxidative status [43], suggesting the existence of different redox phenotypes. Further studies could establish whether the effect of zinc supplementation depends on phenotypic responses to oxidative stress and whether the supplementation can reduce the cellular damage without diminishing the effectiveness of the antineoplastic drugs [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDDP causes the generation of ROS, depletion of GSH, and inhibition of antioxidant enzymes activity. Johns et al (2012) concluded that cisplatin therapy had been shown to induce high levels of lipid peroxidation in lung cancer patients and could be assessed from the 8-isoprostane marker in overnight urine, with or without volume correction (Johns et al, 2012). Thus, the administration of antioxidants such as vitamin C, vitamin E, Silymarin, selenium, and so on before the administration of CDDP has been used to protect against kidney and liver toxicities (Ajith et al, 2009;Abdelmeguid et al, 2010;Ghorbani et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[6] The administration of chemotherapy is also associated with increased free radicals and decreased antioxidants. [78] This oxidant-antioxidant imbalance plays a role in the side effects of chemotherapy drugs as well,[9] for example, cisplatin-induced nephrotoxicity. [10]…”
Section: Introductionmentioning
confidence: 99%